Vocational Profile and Correlates of Employment in People With Schizophrenia: The Role of Avolition - Ang, Mei San; Rekhi, Gurpreet; Lee, Jimmy (Frontiers in Psychiatry, 2020)
Objective Employment was associated with recovery in individuals with schizophrenia. Our study aimed to delineate the vocational profile and investigate factors associated with likelihood of employment in individuals with schizophrenia. Materials and Methods 276 outpatients with schizophrenia were recruited; 274 completed the Positive and Negative Syndrome Scale (PANSS) and Brief Negative Symptom Scale (BNSS). Information on employment status, work outcomes and demographics were collected. Occupation was coded in accordance with the Singapore standard occupational classification. Either BNSS Motivation and Pleasure (MAP) and Emotional Expressivity (EE) or BNSS five-factor (Anhedonia, Asociality, Avolition, Blunted Affect, Alogia) were examined with PANSS factors and demographics in logistic regression with employment status and working full-time as outcome variables. Results One-hundred and twenty-seven (46.01%) participants were employed; 65 (51.18%) worked full-time. In the model with BNSS MAP-EE, MAP (OR=0.897, CI=0.854-0.941) and presence of physical comorbidity (OR=0.533, CI=0.304-0.937) were associated with reduced likelihood of employment; female sex (OR=0.286, CI=0.128 - 0.637) was associated with working part-time. In the model with BNSS five-factor, Avolition (OR=0.541, CI=0.440-0.666) and PANSS Positive (OR=0.924, CI=0.855-0.997) were associated with reduced likelihood of employment; female sex (OR=0.289, CI=0.126 - 0.662) and Avolition (OR=0.644, CI=0.475 - 0.872) were associated with working part-time. Discussion Our study described the vocational profile and correlates of employment in a developed urban Asian country. Negative symptoms, particularly MAP and Avolition, positive symptoms, and physical comorbidity reduced an individual’s likelihood of employment, while female sex and Avolition were associated with working part-time. Efforts to identify and address these factors are necessary to encourage employment in individuals with schizophrenia.